1985
DOI: 10.1007/bf02554913
|View full text |Cite
|
Sign up to set email alerts
|

The role of three-dimensional trabecular microstructure in the pathogenesis of vertebral compression fractures

Abstract: We compared indices of three-dimensional microstructure of iliac trabecular bone between 26 patients with vertebral compression fractures due to postmenopausal osteoporosis and 24 control subjects without vertebral fracture, who were matched for age, sex, race, menopausal status, and several densitometric and histologic indices of both cortical and trabecular bone mass. The patients with fracture had a significantly lower mean value (1.03 +/- 0.15 vs. 1.26 +/- 0.26; P less than 0.005) for indirectly calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
338
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(365 citation statements)
references
References 15 publications
16
338
0
8
Order By: Relevance
“…Previous studies have demonstrated that cancellous bone strength is determined primarily by trabecular geometry; increased cancellous bone strength is strongly associated with increased bone volume and trabecular thickness and by decreased Tb.Pf and SMI. (54)(55)(56) Therefore, our structural results indicate that dasatinib is able to positively affect trabecular bone architecture in normal rats, which is suggestive of an increase in bone strength. The potential effects of dasatinib on bone quality in patients undertaking long-term treatment need further elucidation.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have demonstrated that cancellous bone strength is determined primarily by trabecular geometry; increased cancellous bone strength is strongly associated with increased bone volume and trabecular thickness and by decreased Tb.Pf and SMI. (54)(55)(56) Therefore, our structural results indicate that dasatinib is able to positively affect trabecular bone architecture in normal rats, which is suggestive of an increase in bone strength. The potential effects of dasatinib on bone quality in patients undertaking long-term treatment need further elucidation.…”
Section: Discussionmentioning
confidence: 53%
“…26 site, reduced trabecular separation and higher trabecular number were observed, indicating formation of a more mature bone with a superior mechanical properties and osseointegration process [107,108].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This study provided, for the first time, in vivo evidence for the architectural and mechanistic consequences of postmenopausal bone loss in that fracture subjects had lower surface-to-curve ratio and higher erosion index than their unfractured peers. Although it is well known that osteoporotic bone loss occurs through inhomogeneous resorption, which entails a conversion of plates to rods, along with disconnection of rods (115,117,130), this process had not previously been demonstrated by non-invasive imaging.…”
Section: Clinical Applications Of Trabecular Bone Microstructural Anamentioning
confidence: 99%